Health and health care utilisation among asylum seekers and refugees in the Netherlands: design of a study - Devillé Walter; Bramsen Inge; Gerritsen Annette AM; van Willigen Loes HM; Hovens Johannes E; van der Ploeg Henk M (BMC, 2004)
Abstract Background This article discusses the design of a study on the prevalence of health problems (both physical and mental) and the utilisation of health care services among asylum seekers and refugees in the Netherlands, including factors that may be related to their health and their utilisation of these services. Methods/Design The study will include random samples of adult asylum seekers and refugees from Afghanistan, Iran and Somali (total planned sample of 600), as these are among the largest groups within the reception centres and municipalities in the Netherlands. The questionnaire that will be used will include questions on physical health (chronic and acute diseases and somatization), mental health (Hopkins Symptoms Checklist-25 and Harvard Trauma Questionnaire), utilisation of health care services, pre- and post-migratory traumatic experiences, life-style, acculturation, social support and socio-demographic background. The questionnaire has gone through a translation process (translation and back-translation, several checks and a pilot-study) and cross-cultural adaptation. Respondents will be interviewed by bilingual and bicultural interviewers who will be specifically trained for this purpose. This article discusses the selection of the study population, the chosen outcome measures, the translation and cross-cultural adaptation of the measurement instrument, the training of the interviewers and the practical execution of the study. The information provided may be useful for other researchers in this relatively new field of epidemiological research among various groups of asylum seekers and refugees.